Development of a Novel Therapeutic Approach Using RNA Interference for Targeting Viral Genes - Safiya Sajid (International Journal of Virus Studies, 2024)
RNA interference (RNAi) is a ground breaking therapeutic strategy that holds immense promise for targeting viral genes in the treatment of viral infections. This approach leverages the natural gene-silencing mechanisms of RNAi to inhibit viral replication and expression at the molecular level, providing a precise and adaptable method to counteract viral pathogens, including influenza, HIV, and hepatitis viruses. Recent advancements in RNAi technology have enabled the development of highly specific small interfering RNAs (siRNAs) and microRNAs (miRNAs) that can selectively target and degrade viral mRNA, impeding the virus's life cycle. However, challenges in effective delivery, off-target effects, and immune response activation remain barriers to clinical implementation. This review examines the molecular mechanisms underlying RNAi, explores current advancements in RNAi delivery systems, and evaluates its therapeutic potential and limitations as an antiviral approach. Additionally, we highlight the future directions of RNAi, emphasizing the integration with complementary therapies, such as CRISPR gene editing, to enhance its efficacy and applicability in treating viral infections
Keywords: CRISPR/Cas9; Gene silencing; Immunogenicity; MicroRNA (miRNA); RNA interference (RNAi); RNAi delivery systems; Small interfering RNA (siRNA); Viral gene targeting; antiviral therapy; viral infections